ANALISIS PROFIL KETERAMPILAN PEMECAHAN MASALAH SISWA SMP BERDASARKAN INDIKATOR PISA 2012 - Zubaydah, Aynun; Hidayati, Siti Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the problem-solving profile of seventh-grade junior high school students in Surabaya based on the PISA 2012 indicators. This study used a survey method with a quantitative descriptive approach. The research subjects were 31 seventh-grade students of SMP Negeri 63 Surabaya in the 2025/2026 academic year. The research instrument consisted of 12 questions adapted from PISA questions and arranged based on four problem-solving indicators. The instrument has been validated and has a Cronbach's Alpha reliability coefficient of 0.760. The results showed that 26% of students were in the low category, 55% in the medium category, and 19% in the high category with an average achievement of 53%. The highest indicator was at the stage of integrating and reflecting on results (60%), while the lowest indicator was at the stage of planning and implementing strategies (37%). These findings indicate that students' main weakness lies in developing problem-solving strategies. This study provides an impression of the need for problem-based learning and non-routine contextual practice questions to improve students' problem-solving skills.